SOBOLEVSKITE, TAIMYRITE, AND PT2CUFE (TULAMEENITE?) IN COMPLEX MASSIVE TALNAKHITE ORE, NORIL'SK OREFIELD, RUSSIA - Cook N.J.; Ciobanu C.L.; Merkle R.K.W.; Bernhardt H.-J. (My University, 2002)
Compositional data are given for a suite of minerals present in a particularly PGM-rich ore from Noril'sk region, Russia. A characteristic association of altaite (PbTe) intergrown with sobolevskite (Pd(Bi,Te)) and taimyrite ((Pd,Pt,Cu) 3Sn) occurs within talnakhite-galena-rich ores from the Oktyabr' mine, Noril'sk Complex. Associated minerals include Ag-Au alloy and minor amounts of froodite, paolovite, sperrylite and Pd(Bi,Pb). Varying Bi:Te values in sobolevskite are in agreement with the previo usly proven solid-solution between kotulskite (PdTe) and sobolevskite (PdBi). New compositional and reflectance data are provided for taimyrite with the composition (Pd 1.55Cu0.85Pt0.6)3Sn. An alloy with the composition Pt 2FeCu is common as prismatic and needle-shaped crystals at the outer margin of altaite. This may represent the first report of tulameenite from Noril'sk, albeit morphologically and paragenetically somewhat different from previously reported occurrences. Observed textures, dominated by a range of intergrowths, in part symplectitic, at every scale from cm-size oblong-shaped grains of galena in talnakhite down to m-scale intergrowths of altaite and sobolevskite, derive from a complex sequence of unmixing in the system Pt-Pd-Bi-Te-Pb- Ag-Au-Sn-Cu-Fe-Ni-S-Te during cooling.
Keywords: platinum-group minerals; sobolevskite; taimyrite; tulameenite; Noril’sk; Russia